Analysis of the Sequences, Structures, and Functions of Product-Releasing Enzyme Domains in Fungal Polyketide Synthases - Liu, Lu; Zhang, Zheng; Shao, Chang-Lun; Wang, Chang-Yun (Frontiers in Microbiology, 2017)
Product-releasing enzyme (PRE) domains in fungal non-reducing polyketide synthases (NR-PKSs) play a crucial role in catalysis and editing during polyketide biosynthesis, especially accelerating final biosynthetic reactions accompanied with product offloading. However, up to date, the systematic knowledge about PRE domains is deficient. In the present study, the relationships between sequences, structures and functions of PRE domains were analyzed with 574 NR-PKSs of eight groups (I–VIII). It was found that the PRE domains in NR-PKSs could be mainly classified into three types, thioesterase (TE), reductase (R) and metallo-β-lactamase-type thioesterase (MβL-TE). The widely distributed TE or TE-like domains were involved in NR-PKSs of groups I–IV, VI and VIII. The R domains appeared in NR-PKSs of groups IV and VII, while the physically discrete MβL-TE domains were employed by most NR-PKSs of group V. The changes of catalytic sites and structural characteristics resulted in PRE functional differentiations. The phylogeny revealed that the evolution of TE domains was accompanied by complex functional divergence. The diverse sequence lengths of TE lid-loops affected substrate specificity with different chain lengths. The volume diversification of TE catalytic pockets contributed to catalytic mechanisms with functional differentiations. The above findings may help to understand the crucial catalysis of fungal aromatic polyketide biosyntheses and govern recombination of NR-PKSs to obtain unnatural target products.